Effect of hydrogen bonding strength on the morphology and polymorphism of poly(butylene adipate). Issue 2 (12th March 2020) - Li, Li; Huang, Qigu; Li, Huihui; Sun, Xiaoli; Yan, Shouke
Abstract: The morphology and polymorphism of poly(butylene adipate) (PBA) and its blend with poly(vinyl phenol) (PVPh) or phenoxy are studied. It is identified that the hydrogen bond strength of PBA/PVPh is higher than that of PBA/phenoxy. The ring‐banded structure disappears for PBA/phenoxy, which shows that the formation of a ring‐banded structure cannot directly correlate to the hydrogen bond strength. For the polymorphism of PBA, phenoxy does not influence of the polymorph selection compared to the neat PBA. The crystallization temperature range for the coexistence of α and β crystals of PBA/PVPh is slightly narrowed. The crystallization temperature range for the polymorphism is not consistent with the formation of the ring‐banded structure. Consequently, the ring‐banded spherulites of PBA cannot be correlated to the coexistence of α and β crystals. By contrast, the β‐to‐α transition temperature is affected by the incorporation of phenoxy and PVPh. The β‐to‐α transition temperature increases slightly as blending with phenoxy but significantly as blending with PVPh. This is attributed to the enhanced melting point of β‐PBA due to the formation of thicker lamellae when blending with the amorphous polymer. Thus, the melting of the original β‐PBA and accompanied recrystallization α‐PBA take place at a higher temperature in the blends than that in neat PBA. Abstract : Irregular ring‐banded spherulites formed in poly(butylene adipate) (PBA)/poly(vinyl phenol) blends with strong hydrogen bonding. In contrast, ringless spherulites are observed in PBA/phenoxy blends with weaker hydrogen bonding strength. The formation of ring‐banded structure cannot directly correlate to the hydrogen bond strength. Meanwhile, the crystallization temperature range for polymorphism is not consistent with the formation ring‐band structure. Consequently, the ring‐banded spherulites of PBA cannot be correlated to the coexistence of α and β crystals.